Patterns of alcohol consumption in 16 cohorts of Australian young adults aged 15–24 between 2001 and 2016. (24th January 2020) - Callinan, Sarah; Pennay, Amy; Livingston, Michael; Kuntsche, Emmanuel
Abstract: Background and aims: Repeated cross‐sectional surveys have identified substantial declines in adolescent drinking in Australia and some other countries in recent years. There is debate about whether these declines will be maintained as the cohort ages. This study modelled alcohol consumption over time to check for cohort effects reflecting a decrease in youth consumption, and then used this model to predict how decreases in youth drinking will be sustained through to adulthood. Design: Longitudinal study using data from the Household Income and Labour Dynamics in Australia (HILDA) survey from 2001 to 2016. Piecewise latent growth models were estimated to assess consumption trajectories for each birth cohort from ages 15–18 and 18–24 years. Setting: Australia. Participants: This study focused on 5320 (51.9% female) respondents aged between 15 and 22 in wave 1 (2001) to those aged between 17 and 24 in wave 16 (2016). Measurement: Annual volume of alcohol consumption was calculated as the product of the quantity per occasion and the frequency of drinking expanded to represent drinking occasions per year. Findings: The model with best fit suggested that consumption increased rapidly [ b = 0.667, standard error (SE) = 0.046, P < 0.001] until the legal drinking age of 18 and then plateaued ( b = −0.027, SE = 0.016, P = 0.088). More recent cohorts start with significantly lower levels of consumption ( b = −0.145, SE = 0.010; P < 0.001) but increase at a faster rate ( b = 0.022, SE = 0.003, P < 0.001) between 15 and 18; however, not enough to catch up to earlier cohorts. Conclusion: Recent decreases in adolescent drinking in Australia may, at least in part, be attributed to lower consumption in recent cohorts of younger drinkers. Results indicate that this group may continue to drink less than previous cohorts as they age into their twenties.